Knowledge and Practices on Menstrual Hygiene Management Among Adolescent Girls of Kaski District, Nepal - Poudel, Sasmita; Gautam, Dipesh (International Journal of Social Sciences and Management, 2020)
The study was conducted to understand the cultural and social practices and knowledge prevailing on menstrual hygiene management among adolescent girls in Nepal. A school-based cross-sectional study was conducted among 122 adolescent girls of class VII to X at three schools of Kaski district, Nepal. A pre-tested structured questionnaire was used for assessing socio-demographic profiles, knowledge, and experiences on menstruation, practices (social and cultural) regarding menstrual hygiene management. The data collected were analysed using SPSS version 23 for windows. The mean age at menarche was found to be 12.5±0.9. The majority (73%) girls were aware of menstruation prior to the attainment of it. Most of them got the information from mother (45.9%), the majority (69.7%) used sanitary pad as the absorbents, however, most of them (78.4%) throw the sanitary pad in the garbage. Many cultural and social taboos and restrictions were found associated with menstruation. The majority (91.8%) were not allowed to participate in religious activities, 45.1% were not allowed to touch things in the house, two- thirds (67.2%) were not allowed to cook, and 60.7% were not allowed to enter the kitchen. Most of the adolescent girls were isolated even from normal daily activities and they were not happy with these restrictions during the menstruation. Instead, they urged the need for more support, care, and hygienic practices for proper hygiene management to lead a healthy life. This paper reflects the actual knowledge and practices prevailed in the society during menstruation and emphasizes on providing the correct knowledge on health and helping to correctly practice hygiene during menstruation. Int. J. Soc. Sc. Manage. Vol. 7, Issue-3: 169-175